An Analysis Of Student Difficulties In Writing Narrative Text: A Case Study At Tenth Grade Students Of SMAN 7 Kota Serang - Amira Nuraini; Anggun Nurani; Meillita Puan M; Vyra Pratama (Lembaga Riset dan Inovasi Almatani, 2023)
The aim of this study was to establish the writing difficulties of grade X (tenth) students of SMAN 7 Serang City, especially in the English subject of narrative text sub-chapter. To find out what are the factors that cause difficulties in writing students and grade X (tenth) in English subjects subchapter narrative text. This study used a descriptive qualitative method. Participants in this study were grade X students and took samples from class X.4 SMAN 7 Serang City. As for this study, the data collection technique used was to fill out a questionnaire that had previously been prepared by the researcher. The effects of this study show that each student has difficulties in writing narrative texts. This difficulty focuses on the personality of the student and the way the teacher teaches. The teacher's efforts and students' learning motivation are one way to improve students to learn English. Over time, each student will begin to get used to and begin to understand how to overcome their problems in writing narrative texts properly and correctly.